Penerapan Interpretasi Standar Akuntansi Keuangan (ISAK) Nomor 35 pada laporan keuangan Lembaga Kesejahteraan Sosial Anak (LKSA) di Tondano - Rumagit, Arleina; Karamoy, Herman; Tangkuman, Steven J. (Manajemen Bisnis dan Keuangan Korporat, 2025)
This research aims to understand the application of ISAK Number 35 to non-profit entities, especially the Child Social Welfare Institution (Lembaga Kesejahteraan Sosial Anak/LKSA) as a standard in making financial statements. This research was conducted at LKSA Dorkas Tondano Orphanage and Tondano Good News Orphanage. The types of data used are primary data and secondary data. The research method used in this study is qualitative descriptive. The results of the study show that the financial statements prepared by the Dorkas Orphanage and good news have not implemented ISAK Number 35 in its presentation. This is due to the lack of human resources who understand ISAK Number 35.